Management of patients with issues related to opioid safety, efficacy and/or misuse: a case series from an integrated, interdisciplinary clinic. Issue 1 (December 2016) - Becker, William; Merlin, Jessica; Manhapra, Ajay; Edens, Ellen
Abstract Background Patients, providers, communities and health systems have struggled to achieve balance between access to opioid treatment for chronic pain and its potential harmful consequences: especially misuse, addiction and overdose. We developed an interdisciplinary clinic embedded within primary care (the Opioid Reassessment Clinic—ORC) with the goal of improving the quality of care of patients with co-occurring chronic pain and issues related to opioid safety, efficacy and/or misuse. Case descriptions We present three cases referred to the ORC that highlight complex clinical scenarios related to assessment and treatment of patients with chronic pain and issues related to opioid safety, efficacy and misuse. Discussion and evaluation In the context of the three cases, with respect to assessment, we discuss: making the diagnosis of opioid use disorder; allowing the patient space to endorse lack of efficacy; identification of co-occurring hazardous alcohol use; and recognizing barriers to multimodal pain care. With respect to treatment, we discuss: making a change in treatment with which the patient may not agree; effectiveness of buprenorphine/naloxone for the treatment of chronic pain; responding to low efficacy; and making continued opioid therapy contingent on engagement with substance abuse treatment. Conclusions The core components of our approach—biopsychosocial assessment and multimodal treatment planning with an emphasis on promoting functional goals and safety using clear communication and a patient-centered stance—should guide providers in the management of similar clinical scenarios. More evidence is needed to definitively guide specific interventions and points of clinical equipoise.